Nearer of boundary - Mesa Saldarriaga, Sergio (Estudios de Filosofía, 2000)
The concept of autonomy of music has been discussed in terms of musical genres and of structural parameters. This paper exposes the historical steps leading to the concept of Music, as known by the classical tradition, and the reflection about the instrumental music, that consolidates the idea of absolute music. This idea, on its turn, has two meanings: music as texts and emotions free, and music as absolute and utmost language. The paper finally studies today way of understanding autonomy of music: music arises from the very structure of sounds, without immediately appealing to the rhetoric model or to the harmonic logic.